Cote d'Ivoire : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economy proved resilient to Covid-19 and continued recovering in 2021, with growth estimated at 7 percent. Growth is forecasted to slow to 6 percent this year due to the war in Ukraine. Inflation increased to 4.2 percent last year, on the back of surging food prices, and is expected at 5.5 percent this year, while the current account deficit is projected to reach 4.8 percent of GDP. Risks are tilted to the downside, as a result of the war in Ukraine, global financing conditions, and regional instability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Cote d'Ivoire